THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL BEHAVIOR AND INCOME ON INVESTMENT DECISION - Arianti, Baiq Fitri (EAJ (Economic and Accounting Journal), 2018)
This research aims to analyze and measure the influence of financial literacy, financial behavior and income on investment decisions. The type of research used is quantitative research descriptive method. Types and data sources used are primary data that is data collected and processed by the researcher himself from the object. The amount of population in this research is 29.231 student and the sample technique used is randomsampling by using slovin formula. Data were collected by using questionnaire method from 100 student become sample in this research. Data analysis techniques used in this research are descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression test, F test, t test and coefficient of determination with the helpof software program SPSS version 22. The results of this research indicate that financial literacy no significant effect on investment decisions, while financial and income behavior have a significant effect on investment decisions.